Re-examination of the crab spider species Oxytate minuta Tang, Yin et Peng, 2005 (Araneae: Thomisidae) - Jin, Chi; Zhang, Feng (Zootaxa, 2012)
The genus Indoxysticus, established by Benjamin and Jaleel in 2010 with the type species Xysticus minutus (Tikader, 1960), differs from other thomisids by the oval spermathecae with well-defined chambers in the female and by the broad-based embolus in the male (Benjamin & Jaleel 2010). At present, the genus includes only two species, I. minutus (Tikader, 1960) and I. lumbricus Tang & Li, 2010 (Platnick 2012), which are known from India and China, respectively (Tikader 1960; Tang & Li 2010).